E-Learning-Based Collaborative as an Effort to Reduce High School Students' Misconceptions of Heat - Haryono, Heny Ekawati; Jatmiko , Budi; Prahani , Binar Kurnia; Zayyadi , Moh.; Kaniawati , Ida; Kurtuluş, Muhammed Akif (Jurnal Pendidikan IPA Indonesia, 2024)
The purpose of this study was to determine the effect of E-learning-based collaborative learning in reducing students' misconceptions about class heat material. This study used a pre-experimental design with a one-group pretest-posttest design. The sampling technique used purposive sampling. The sample used was 300 grade XI high school students. Student misconceptions were analyzed using the CRI (Certainty of Response Index) method. The results showed that student misconceptions decreased by 26.50% from an average of 54.00% before learning to 27.50% after implementing E-learning-based collaborative learning. Based on the results of the hypothesis test, it can be concluded that e-learning-based collaborative learning has proven effective in reducing high school students' misconceptions regarding the concept of heat. The novelty of this study lies in the integration of cooperative learning with an e-learning platform that is specifically designed to reduce misconceptions about the idea of heat at the Senior High School.